Dietary factors associated with lifetime asthma or hayfever diagnosis in Australian middle-aged and older adults: a cross-sectional study - Rosenkranz, Richard R.; Rosenkranz, Sara K.; Neessen, Kelly J. J. (My University, 2012)
Background: There is abundant research relevant to genetic and environmental influences on asthma and hayfever, but little is known about dietary risk factors in Australian adults. This study’s purpose was to identify dietary factors associated with lifetime asthma (AS) and asthma or hayfever (AS/HF) diagnosis in Australian middle-aged and older adults. Methods: From The 45 and Up Study baseline self-report data, this study included 156,035 adult men and women. Participants were sampled from the general population of New South Wales, Australia in 2006–2009. About 12% of participants reported ever receiving an AS diagnosis (men 10%; women 14%) and 23% reported AS/HF diagnosis (men 19%; women 26%). Following principle components factor analysis, dietary items loaded onto one of four factors for men (meats/cheese; fruits/vegetables; poultry/seafood; grains/alcohol) or five factors for women (meats; fruits/vegetables; poultry/seafood; cereal/alcohol; brown bread/cheese). Logistic regression was used to analyze the associations between dietary factors and AS or AS/HF diagnosis. Results: For men, the meats/cheese factor was positively associated with AS (AOR = adjusted odds ratio for highest versus lowest quintile = 1.18, 95%CI = 1.08, 1.28; P[subscript trend] = 0.001) and AS/HF (AOR for highest versus lowest quintile = 1.22, 95%CI = 1.14, 1.29; P[subscript trend] < 0.001). Poultry/seafood was also associated with AS/HF in men (AOR for highest versus lowest quintile = 1.11, 95%CI = 1.04, 1.17; P[subscript trend] = 0.002). For women, significant risk factors for AS/HF included meats (AOR for highest versus lowest quintile = 1.25, 95%CI = 1.19, 1.31; P[subscript trend] = 0.001), poultry/seafood (AOR for highest versus lowest quintile = 1.06, 95%CI = 1.01, 1.12; P[subscript trend] = 0.016), and fruits/vegetables (AOR for highest versus lowest quintile = 1.07, 95%CI = 1.02, 1.12; P[subscript trend] = 0.011). In contrast, the cheese/brown bread dietary factor was protective against AS in women (AOR for highest versus lowest quintile = 0.88, 95%CI = 0.82, 0.94; P[subscript trend] < 0.001). Conclusions: Generally, diets marked by greater intakes of meats, poultry, and seafood were associated with diagnosed AS and AS/HF. Taken together, these findings suggest that adherence to a more meat-based diet may pose risk for AS and AS/HF in Australian adults.
Keywords: Asthma; Hayfever; Airway health; Diet; Western diet; Meat; Adult; Older adults